Nab2p and the Thp1p-Sac3p Complex Functionally Interact at the Interface between Transcription and mRNA Metabolism - Mercedes Gallardo; Rosa Luna; Hediye Erdjument‐Bromage; Paul Tempst; Andrés Aguilera (2003)
THP1 is a conserved eukaryotic gene whose null mutations confer, in yeast, transcription and genetic instability phenotypes and RNA export defects similar to those of the THO/TREX complex null mutations. In a search for multicopy suppressors of the transcription defect of thp1Δ cells, we identified the poly(A)+ RNA-binding heterogeneous nuclear ribonucleoprotein Nab2p. Multicopy NAB2 also suppressed the RNA export defect of thp1Δ cells. This result suggests a functional relationship between Thp1p and Nab2p. Consistently, the leaky mutation nab2-1 conferred a transcription defect and hyper-recombination phenotype similar to those of thp1Δ, although to a minor degree. Reciprocally, a purified His6-tagged Thp1p fusion bound RNA in vitro. In a different approach, we show by Western analyses that a highly purified Thp1p-Sac3p complex does not contain components of THO/TREX and that sac3Δ confers a transcription defect and hyper-recombination phenotype identical to those of thp1Δ. mRNA degradation was not affected in thp1Δ mutants, implying that their expression defects are not due to mRNA decay. This indicates that Thp1p-Sac3p is a structural and functional unit. Altogether, our results suggest that Thp1p-Sac3p and Nab2p are functionally related heterogeneous nuclear ribonucleoproteins that define a further link between mRNA metabolism and transcription. THP1 is a conserved eukaryotic gene whose null mutations confer, in yeast, transcription and genetic instability phenotypes and RNA export defects similar to those of the THO/TREX complex null mutations. In a search for multicopy suppressors of the transcription defect of thp1Δ cells, we identified the poly(A)+ RNA-binding heterogeneous nuclear ribonucleoprotein Nab2p. Multicopy NAB2 also suppressed the RNA export defect of thp1Δ cells. This result suggests a functional relationship between Thp1p and Nab2p. Consistently, the leaky mutation nab2-1 conferred a transcription defect and hyper-recombination phenotype similar to those of thp1Δ, although to a minor degree. Reciprocally, a purified His6-tagged Thp1p fusion bound RNA in vitro. In a different approach, we show by Western analyses that a highly purified Thp1p-Sac3p complex does not contain components of THO/TREX and that sac3Δ confers a transcription defect and hyper-recombination phenotype identical to those of thp1Δ. mRNA degradation was not affected in thp1Δ mutants, implying that their expression defects are not due to mRNA decay. This indicates that Thp1p-Sac3p is a structural and functional unit. Altogether, our results suggest that Thp1p-Sac3p and Nab2p are functionally related heterogeneous nuclear ribonucleoproteins that define a further link between mRNA metabolism and transcription. In eukaryotes, the processing and export of mRNA from the nuclear transcription site to the cytoplasm require a large number of proteins, a fraction of which act cotranscriptionally. RNA polymerase II (pol II) 1The abbreviations used are: pol II, RNA polymerase II; hnRNP, heterogeneous nuclear ribonucleoprotein; mRNP, mRNA and heterogeneous nuclear ribonucleoprotein complex; HA, hemagglutinin; MALDI-reTOF, matrix-assisted laser desorption ionization reflectron time-of-flight; SC medium, synthetic complete medium; dsDNA, double-stranded DNA. 1The abbreviations used are: pol II, RNA polymerase II; hnRNP, heterogeneous nuclear ribonucleoprotein; mRNP, mRNA and heterogeneous nuclear ribonucleoprotein complex; HA, hemagglutinin; MALDI-reTOF, matrix-assisted laser desorption ionization reflectron time-of-flight; SC medium, synthetic complete medium; dsDNA, double-stranded DNA.-driven transcription elongation is coupled with 5′-end capping, splicing, 3′-end cleavage, and poly(A)+ addition (1Hirose Y. Manley J.L. Genes Dev. 2000; 14: 1415-1429Google Scholar, 2Proudfoot N.J. Furger A. Dye M.J. Cell. 2002; 108: 501-512Google Scholar). Thus, capping enzymes access the 5′-end of nascent mRNAs via the pol II C-terminal domain; splicing occurs cotranscriptionally in association with the transcription elongation complex via the pol II C-terminal domain (3Mortillaro M.J. Blencowe B.J. Wei X. Nakayasu H. Du L. Warren S.L. Sharp P.A. Berezney R. Proc. Natl. Acad. Sci. U. S. A. 1996; 93: 8253-8257Google Scholar, 4Steinmetz E.J. Cell. 1997; 89: 491-494Google Scholar, 5Vincent M. Lauriault P. Dubois M.F. Lavoie S. Bensaude O. Chabot B. Nucleic Acids Res. 1996; 24: 4649-4652Google Scholar, 6Yuryev A. Patturajan M. Litingtung Y. Joshi R.V. Gentile C. Gebara M. Corden J.L. Proc. Natl. Acad. Sci. U. S. A. 1996; 93: 6975-6980Google Scholar); and cleavage of the poly(A)+ site is dependent on the pol II C-terminal domain (7McCracken S. Fong N. Yankulov K. Ballantyne S. Pan G. Greenblatt J. Patterson S.D. Wickens M. Bentley D.L. Nature. 1997; 385: 357-361Google Scholar). The connection between transcription and mRNA metabolism is supported by the accumulation of unspliced pre-mRNAs in mutants with a truncated pol II C-terminal domain (8Misteli T. Spector D.L. Mol. Cell. 1999; 3: 697-705Google Scholar) or the retention at the site of transcription of human β-globin pre-mRNAs defective in either splicing or 3′-end formation (9Custodio N. Carmo-Fonseca M. Geraghty F. Pereira H.S. Grosveld F. Antoniou M. EMBO J. 1999; 18: 2855-2866Google Scholar). This connection is also extended to mRNA export. The mRNA is not exported from the nucleus unless the transcript has been properly processed (10Zenklusen D. Stutz F. FEBS Lett. 2001; 498: 150-156Google Scholar).Nuclear mRNA export seems to be connected to transcription at both functional and physical levels. It has been shown that hyperadenylated transcripts accumulate at the site of transcription after different mRNA export blockages (11Jensen T.H. Patricio K. McCarthy T. Rosbash M. Mol. Cell. 2001; 7: 887-898Google Scholar). Importantly, a conserved TREX complex that contains Sub2p/UAP56, Yra1p/ALY, Tex1p, and the THO complex has been identified in yeast and humans (12Strasser K. Masuda S. Mason P. Pfannstiel J. Oppizzi M. Rodriguez-Navarro S. Rondón A.G. Aguilera A. Struhl K. Reed R. Hurt E. Nature. 2002; 417: 304-308Google Scholar). Yra1p/ALY and Sub2p/UAP56 are both involved in mRNA nuclear export (13Reed R. Hurt E. Cell. 2002; 108: 523-531Google Scholar). THO was previously identified as a four protein-containing complex involved in transcription elongation and the maintenance of genome stability (14Chávez S. Beilharz T. Rondón A.G. Erdjument-Bromage H. Tempst P. Svejstrup J.Q. Lithgow T. Aguilera A. EMBO J. 2000; 19: 5824-5834Google Scholar). Yeast mutations in any of the four genes encoding the THO complex (THO2, HPR1, MFT1, and THP2) confer transcription elongation defects and a strong hyper-recombination phenotype that is transcription-dependent (14Chávez S. Beilharz T. Rondón A.G. Erdjument-Bromage H. Tempst P. Svejstrup J.Q. Lithgow T. Aguilera A. EMBO J. 2000; 19: 5824-5834Google Scholar, 15Chávez S. Aguilera A. Genes Dev. 1997; 11: 3459-3470Google Scholar, 16Piruat J.I. Aguilera A. EMBO J. 1998; 17: 4859-4872Google Scholar). Functional analysis of sub2 and yra1 mutants as well as mex67 and mtr2 mutants, defective in the Mtr2p-Mex67p essential heterodimeric mRNA export factor (17Santos-Rosa H. Moreno H. Simos G. Segref A. Fahrenkrog B. Pante N. Hurt E. Mol. Cell. Biol. 1998; 18: 6826-6838Google Scholar, 18Segref A. Sharma K. Doye V. Hellwig A. Huber J. Luhrmann R. Hurt E. EMBO J. 1997; 16: 3256-3271Google Scholar), revealed that they have defective transcription and high levels of transcription-dependent direct-repeat recombination (19Jimeno S. Rondón A.G. Luna R. Aguilera A. EMBO J. 2002; 21: 3526-3535Google Scholar). All these factors represent a subset of conserved eukaryotic proteins involved in mature mRNA biogenesis and processing steps that are important for efficient transcription. Regardless of the specific function of these factors along the different steps of mRNA metabolism from 5′-end capping to 3′-end cleavage, poly(A)+ addition, and export, failure to perform appropriately any of these steps may affect the other steps, leading to nuclear mRNA accumulation and transcription impairment and causing transcription-associated hyper-recombination.In a recent search for yeast mutants with high levels of genetic instability, we identified THP1, a gene conserved in eukaryotes whose null mutations confer the same transcription defect and hyper-recombination phenotype as those of THO mutants (20Gallardo M. Aguilera A. Genetics. 2001; 157: 79-89Google Scholar). To gain new insight into Thp1p function, we undertook two experimental approaches. First, in a search for multicopy suppressors of the gene expression defect of thp1Δ, we identified NAB2, a gene encoding an hnRNP that specifically associates with nuclear poly(A)+ RNA in vivo (21Anderson J.T. Wilson S.M. Datar K.V. Swanson M.S. Mol. Cell. Biol. 1993; 13: 2730-2741Google Scholar) and is required for poly(A) tail length control and nuclear RNA export (22Green D.M. Marfatia K.A. Crafton E.B. Zhang X. Cheng X. Corbett A.H. J. Biol. Chem. 2002; 277: 7752-7760Google Scholar, 23Hector R.E. Nykamp K.R. Dheur S. Anderson J.T. Non P.J. Urbinati C.R. Wilson S.M. Minvielle-Sebastia L. Swanson M.S. EMBO J. 2002; 21: 1800-1810Google Scholar). Second, we purified the Thp1p-Sac3p complex, which has also been purified in a parallel study (24Fischer T. Strasser K. Racz A. Rodriguez-Navarro S. Oppizzi M. Ihrig P. Lechner J. Hurt E. EMBO J. 2002; 21: 5843-5852Google Scholar); characterized it for the presence of components of the THO/TREX complex; and determined whether Thp1p-Sac3p acts as a functional unit in mRNP metabolism. Sac3p was first identified as an actin suppressor (25Novick P. Osmond B.C. Botstein D. Genetics. 1989; 121: 659-674Google Scholar) and has been shown to be involved in nuclear protein export (26Jones A.L. Quimby B.B. Hood J.K. Ferrigno P. Keshava P.H. Silver P.A. Corbett A.H. Proc. Natl. Acad. Sci. U. S. A. 2000; 97: 3224-3229Google Scholar) and recently in RNA export (24Fischer T. Strasser K. Racz A. Rodriguez-Navarro S. Oppizzi M. Ihrig P. Lechner J. Hurt E. EMBO J. 2002; 21: 5843-5852Google Scholar, 27Lei E.P. Stern C.A. Fahrenkrog B. Krebber H. Moy T.I. Aebi U. Silver P.A. Mol. Biol. Cell. 2003; 14: 836-847Google Scholar). We show by genetic and molecular analyses that sac3Δ and nab2-1 strains have transcription and hyper-recombination phenotypes similar to those of thp1Δ. In addition, we show that purified His6-Thp1p from Escherichia coli binds RNA in vitro. We conclude that Nab2p and Thp1p-Sac3p are functionally related hnRNP-like factors that act in the same process as THO/TREX and Mtr2p-Mex67p in mRNP metabolism.EXPERIMENTAL PROCEDURESStrains—We used the wild-type (W303-1A), hpr1Δ::HIS3 (U678-1C), tho2Δ::KAN (RK2-6C) (16Piruat J.I. Aguilera A. EMBO J. 1998; 17: 4859-4872Google Scholar), thp1Δ::KAN (WFBE046) (20Gallardo M. Aguilera A. Genetics. 2001; 157: 79-89Google Scholar), and mex67-5 (WMC1-1A) (19Jimeno S. Rondón A.G. Luna R. Aguilera A. EMBO J. 2002; 21: 3526-3535Google Scholar) strains that have been reported previously. Strain LSY267 (pep4Δ) (28Symington L.S. EMBO J. 1991; 10: 987-996Google Scholar) isogenic to W303-1A was used for protein complex purification. Mutant nab2-1 (22Green D.M. Marfatia K.A. Crafton E.B. Zhang X. Cheng X. Corbett A.H. J. Biol. Chem. 2002; 277: 7752-7760Google Scholar) is a nab2Δ strain carrying the nab2-1 mutant allele in a centromeric plasmid. The sac3Δ::KAN (Y03517) and thp1Δ::KAN (Y01764) strains were obtained from EUROSCARF (Frankfurt, Germany). Isogenic derivatives were obtained by genetic crosses. These include wild-type strains SAY3-2B, NAL-3A, and NAL-3B and mutant strains SAY3-2A (sac3Δ) and NAL-11B and NAL-5B (nab2-1). All comparative analyses were performed with mutants and their isogenic wild-type strains on either the W303 (R. Rothstein) or BY4741 (EUROSCARF) genetic background, with the exception of nab2-1, for which we used its own genetic background (22Green D.M. Marfatia K.A. Crafton E.B. Zhang X. Cheng X. Corbett A.H. J. Biol. Chem. 2002; 277: 7752-7760Google Scholar).Plasmids—Plasmids p416-GAL1-lacZ and pSCh202 (15Chávez S. Aguilera A. Genes Dev. 1997; 11: 3459-3470Google Scholar), used for the studies of recombination and transcription, and plasmids YEp351-SUB2 (19Jimeno S. Rondón A.G. Luna R. Aguilera A. EMBO J. 2002; 21: 3526-3535Google Scholar) and pSUP38 (16Piruat J.I. Aguilera A. EMBO J. 1998; 17: 4859-4872Google Scholar) have been published previously. pRS316LΔNS and pRS316L are identical to pRS314LΔNS and pRS314L (29Prado F. Piruat J.I. Aguilera A. EMBO J. 1997; 16: 2826-2835Google Scholar), but in vector pRS316. For the isolation of multicopy suppressors of thp1Δ, we used the pCM184-LAUR plasmid (19Jimeno S. Rondón A.G. Luna R. Aguilera A. EMBO J. 2002; 21: 3526-3535Google Scholar). We used MW90 constructed in YEp351 as a yeast multicopy library (30Waldherr M. Ragnini A. Jank B. Teply R. Wiesenberger G. Schweyen R.J. Curr. Genet. 1993; 24: 301-306Google Scholar).For the purification of Thp1p from E. coli, we constructed plasmid pT7-HA-THP1 containing an N-terminal His6-HA-Thp1p translational fusion under the control of the T7 RNA polymerase promoter. For this purpose, the HA-THP1 fragment was obtained by PCR using primers GATATCATCGATCTCGAGTCACCAAAGAACGTGAG and GGATCCTCTAGAGCTAGCTATCCCTATGACGTTCCCTCTCACGTTTTGTGGTCCATGGAAAAGAGAAG and subcloned into the NheI-ClaI site of plasmid pT7-7-His6 (31Clever B. Intherthal H. Schmuckli-Maurer J. King J. Sigrist M. Heyer W.D. EMBO J. 1997; 16: 2535-2544Google Scholar).Purification of His6-HA-Thp1p from E. coli—E. coli strain BL21(DE3) transformed with plasmid pT7-HA-THP1 was grown in 1 liter of LB medium supplemented with 100 μg/ml ampicillin up to A600 = 0.8. Expression was induced for 4 h by adding isopropyl-β-d-thiogalactopyranoside to a final concentration of 0.5 mm. Cells were lysed in buffer A (50 mm NaH2PO4 and 300 mm NaCl, pH 8) containing 10 mm imidazole. His6-HA-Thp1 was partially purified by affinity chromatography on a nickel-nitrilotriacetic acid column (QIAGEN Inc.) in buffer A containing increasing concentrations of imidazole (20 and 250 mm).Thp1p-Sac3p Complex Purification and Western Analyses—The Thp1p-Sac3p complex was purified using a C-terminally TAP-tagged Thp1 protein constructed for this study. For this, we replaced the wild-type copy of THP1 with the THP1-TAP fusion obtained by PCR with primers GTTAATGAACGAATCACCAAGATGTTTCCTGCCCATTCTCACGTTTTGTGGTCCATGGAAAAGAGAAG and CAGCATAATGTCGCTCCTTCTCTTCTATTTCCTATATATATCTACGACTCACTATAGGG in wild-type strain LSY267. Purified TAP-tagged proteins were purified essentially as described (32Rigaut G. Shevchenko A. Rutz B. Wilm M. Mann M. Seraphin B. Nat. Biotechnol. 1999; 17: 1030-1032Google Scholar) with modifications as published (19Jimeno S. Rondón A.G. Luna R. Aguilera A. EMBO J. 2002; 21: 3526-3535Google Scholar). Purified complexes were run on a 10% SDS-polyacrylamide gel and transferred to nylon membranes. After blocking with phosphate-buffered saline containing 0.1% Tween 20 and 5% milk, proteins were detected using antibodies against Mft1p and Sub2p and peroxidase-conjugated goat anti-rabbit IgG. Blots were washed with phosphate-buffered saline and 0.1% Tween 20 and developed by enhanced chemiluminescence reactions (ECL, Amersham Biosciences).Protein Identification—Gel-resolved proteins were digested with trypsin and partially fractionated, and the resulting peptide mixtures were analyzed by matrix-assisted laser desorption ionization reflectron time-of-flight (MALDI-reTOF) mass spectrometry (Reflex III, Bruker Daltonics, Bremen, Germany) as described (33Erdjument-Bromage H. Lui M. Lacomis L. Grewal A. Annan R.S. McNulty D.E. Carr S.A. Tempst P. J. Chromatogr. A. 1998; 826: 167-181Google Scholar) and also using an electrospray ionization triple quadrupole tandem mass spectrometry instrument (API300, ABI/MDS Sciex, Thornhill, Canada) modified with an ultrafine ionization source (34Geromanos S. Frecklenton G. Tempst P. Anal. Chem. 2000; 72: 777-790Google Scholar). Selected masses from the MALDI-reTOF spectra were taken to search the yeast segment of a protein non-redundant data base. Tandem mass spectra were inspected for y″ ion series to compare with the computer-generated fragment ion series of the predicted tryptic peptides.mRNA Export Assays—In situ mRNA localization assays were performed as described (35Amberg D.C. Goldstein A.L. Cole C.N. Genes Dev. 1992; 6: 1173-1189Google Scholar) using digoxigenin-labeled oligo(dT)16.In Vitro RNA and DNA Binding Assays—In vitro RNA and DNA band shifting assays were performed following the procedures described previously (19Jimeno S. Rondón A.G. Luna R. Aguilera A. EMBO J. 2002; 21: 3526-3535Google Scholar) using identical RNA and DNA probes.Miscellaneous—Recombination frequencies were obtained from two to three different transformants for each genotype. They were determined as the median frequency of 6–12 independent values for each transformant as reported previously (29Prado F. Piruat J.I. Aguilera A. EMBO J. 1997; 16: 2826-2835Google Scholar). β-Galactosidase assays and Northern analyses were performed according to previously published procedures (15Chávez S. Aguilera A. Genes Dev. 1997; 11: 3459-3470Google Scholar).RESULTSMulticopy NAB2 Suppresses the Gene Expression Defect of thp1Δ—To obtain new insights into the functional role of Thp1p, we searched for genes that could potentially have an overlapping function with Thp1p. For this, we used our newly developed genetic assays for the analysis of gene expression based on plasmid pCM184-LAUR carrying a 4.15-kb lacZ-URA3 translational fusion under the control of the Ptet promoter (Fig. 1A) (19Jimeno S. Rondón A.G. Luna R. Aguilera A. EMBO J. 2002; 21: 3526-3535Google Scholar). We have previously reported that thp1Δ mutants are defective in transcription of the lacZ sequence (20Gallardo M. Aguilera A. Genetics. 2001; 157: 79-89Google Scholar). Here, we first showed that, as expected, thp1Δ mutants containing the LAUR expression system were unable to form colonies on synthetic complete medium without uracil (SC–Ura) and showed reduced levels of β-galactosidase activity (Fig. 1B) (data not shown).From ∼80,000 thp1Δ transformants with the multicopy library MW90 (30Waldherr M. Ragnini A. Jank B. Teply R. Wiesenberger G. Schweyen R.J. Curr. Genet. 1993; 24: 301-306Google Scholar) plated on SC–Ura, we selected one that recovered the capacity to grow in the absence of uracil. Isolation and restriction and sequencing analysis of the plasmid (YEp351-1.9) carried by this transformant revealed a 6.5-kb insert of the NAB2 region covering three complete open reading frames. Complementation analysis of deletion derivative versions of the original plasmid indicated that the ability of this plasmid to suppress the gene expression defect of thp1Δ was abolished only if NAB2, but not the other two open reading frames, was deleted (data not shown). Subcloning of the NAB2 open reading frame into YEp351 confirmed that multicopy NAB2, and not the adjacent genes of the original insert, suppressed the inability of thp1Δ cells to express the lacZ-URA3 fusion as determined by growth on SC–Ura and by Northern analysis (Fig. 1, B and C). This suppression was specific to thp1Δ, and not to other mutants with the thp1-like phenotype such as hpr1Δ and tho2Δ (Fig. 1B). Quantification of mRNA levels showed that suppression of the transcription defect of thp1Δ cells was partial. Multicopy NAB2 made thp1Δ cells reach 11.6% of the wild-type levels of lacZ-URA3 expression.Finally, recombination analyses of the chromosomal direct-repeat system leu2-k::ADE2-URA3::leu2-k showed that multicopy NAB2 reduced recombination in a thp1Δ background to levels (1.1 × 10–1) 1.5-fold below thp1 levels (7.1 × 10–2). These results indicate that suppression of thp1Δ by NAB2 overexpression is partial. It is detectable at the transcriptional level, but it is not enough to yield a significant effect on direct-repeat recombination.Multicopy NAB2 Partially Suppresses the mRNA Export Defect of thp1Δ Mutants—Given the phenotypic similarity of thp1Δ mutants to mRNA export mutants and THO/TREX mutants (12Strasser K. Masuda S. Mason P. Pfannstiel J. Oppizzi M. Rodriguez-Navarro S. Rondón A.G. Aguilera A. Struhl K. Reed R. Hurt E. Nature. 2002; 417: 304-308Google Scholar, 19Jimeno S. Rondón A.G. Luna R. Aguilera A. EMBO J. 2002; 21: 3526-3535Google Scholar), we first showed, by in situ hybridization with digoxigenin-labeled oligo(dT) and fluorescein-conjugated anti-digoxigenin antibody, that Thp1p was also required for proper mRNA nuclear export at both 30 and 37 °C (Fig. 1D) (data not shown). This is agreement with recently reported data from a parallel study (24Fischer T. Strasser K. Racz A. Rodriguez-Navarro S. Oppizzi M. Ihrig P. Lechner J. Hurt E. EMBO J. 2002; 21: 5843-5852Google Scholar). Consistent with this result, we observed that thp1Δ mex67-5 and sac3Δ mex67-5 double mutants were also inviable (data not shown), a phenotype previously observed for mutants that accumulate mRNA in the nucleus (18Segref A. Sharma K. Doye V. Hellwig A. Huber J. Luhrmann R. Hurt E. EMBO J. 1997; 16: 3256-3271Google Scholar, 19Jimeno S. Rondón A.G. Luna R. Aguilera A. EMBO J. 2002; 21: 3526-3535Google Scholar, 36Strasser K. Bassler J. Hurt E. Cell Biol. 2000; 150: 695-706Google Scholar).Nab2p is a major nuclear protein associated with nuclear poly(A)+ RNA (21Anderson J.T. Wilson S.M. Datar K.V. Swanson M.S. Mol. Cell. Biol. 1993; 13: 2730-2741Google Scholar) required for nuclear mRNA export (22Green D.M. Marfatia K.A. Crafton E.B. Zhang X. Cheng X. Corbett A.H. J. Biol. Chem. 2002; 277: 7752-7760Google Scholar, 23Hector R.E. Nykamp K.R. Dheur S. Anderson J.T. Non P.J. Urbinati C.R. Wilson S.M. Minvielle-Sebastia L. Swanson M.S. EMBO J. 2002; 21: 1800-1810Google Scholar). As the transcription defect of thp1Δ was accompanied by mRNA accumulation in the nucleus, we assayed whether this phenotype was also suppressed by multicopy NAB2. As shown in Fig. 1D, thp1Δ cells carrying multicopy NAB2 showed significantly lower nuclear accumulation of poly(A)+ RNA compared with thp1Δ cells, even though some nuclear mRNA accumulation could still be observed after 4 h of shifting cells to 37 °C. These results confirm that thp1Δ is suppressed by multicopy NAB2, but only at partial levels, and that the gene expression and mRNA export phenotypes are linked.nab2-1 Strains Are Defective in lacZ Transcription and Stimulate Direct-repeat Recombination—As our results showing that multicopy NAB2 suppresses thp1Δ suggest that the function of Nab2p might be related to that of Thp1p, we investigated whether nab2 mutants also show expression and recombination phenotypes similar to the those of thp1Δ mutants. Because NAB2 is an essential gene, we used nab2-1 for our studies. This mutation is leaky at 30 °C, and it was previously shown that nab2-1 strains accumulate mRNA in the nucleus at this temperature (22Green D.M. Marfatia K.A. Crafton E.B. Zhang X. Cheng X. Corbett A.H. J. Biol. Chem. 2002; 277: 7752-7760Google Scholar). As shown in Fig. 2A, nab2-1 reduced β-galactosidase activity to 20% of the wild-type levels. Kinetic analyses of transcription of the GAL1pr::lacZ and GAL1pr::PHO5 fusion constructs revealed that lacZ mRNA accumulated at a much slower rate than the wild-type strains, whereas only a small difference was found for PHO5. As shown for thp1Δ, this implies that the main transcription step impaired in nab2-1 mutants is transcription through lacZ, and not activation of the GAL1 promoter. Next, we determined the effect of nab2-1 on recombination between direct repeats. For this, we constructed nab2-1 strains carrying the chromosomal direct-repeat system leu2-k::ADE2-URA3::leu2-k containing two 2.16-kb repeat units. Recombination between the leu2-k repeats was scored in this system as deletions that lose the ADE2-URA3 intervening sequence plus one leu2-k copy. The frequency of deletions of nab2-1 strains was 25-fold above wild-type levels (Fig. 2B). The intensity of the phenotypes of nab2-1 was weaker than that of the phenotypes of thp1Δ, but this may be due to the leaky activity of the nab2-1 allele (22Green D.M. Marfatia K.A. Crafton E.B. Zhang X. Cheng X. Corbett A.H. J. Biol. Chem. 2002; 277: 7752-7760Google Scholar). To conclude, nab2-1 shows a transcription defect and hyper-recombination phenotype similar to those of thp1Δ, although to a lesser degree.Fig. 2Expression analysis of GAL1pr::lacZ and GAL1pr::PHO5 constructs in nab2-1 mutants.A: upper panels, β-galactosidase and acid phosphatase activities of the wild-type (WT; NAL-3A) and nab2-1 (NAL-11B) strains transformed with plasmids p416-GAL1-lacZ and pSCh202. Each value represents the average of two to three different transformants. Only the data of induced expression (2% galactose) are given. Under repression conditions (2% glucose), values were below detection levels in all cases. Lower panels, Northern analysis of lacZ and PHO5 mRNAs driven by the GAL1 promoter. Mid-log phase cells transformed with plasmid p416-GAL1-lacZ or pSCh202 were diluted in 3% glycerol- and 2% lactate-containing SC–Ura to A600 = 0.5 and incubated for 16 h at 30 °C. Galactose was then added, and samples were taken at different times as indicated. The 0.9-kb PHO5 EcoRV internal fragment was used as the PHO5 probe. For other details, see the legend to Fig. 1. B: recombination frequencies of the chromosomal direct-repeat system leu2-k::URA3-ADE2::leu2-k in the wild-type (NAL-3B) and nab2-1 (NAL-5B) strains. All experiments were performed at 30 °C. Recombination values are the median of a total of 12 independent colonies obtained from SC medium. Ura– recombinants were scored on SC medium containing 5-fluoroorotic acid. A.U., arbitrary units.View Large Image Figure ViewerDownload (PPT)mRNA Degradation Rates Are Unaffected in thp1Δ Mutants—The observation that transcription driven by the same promoter is defective in thp1Δ cells for some DNA sequences (i.e. lacZ), but not for others (i.e. PHO5), indicates that the transcription defect occurs at a post-initiation step (20Gallardo M. Aguilera A. Genetics. 2001; 157: 79-89Google Scholar). The fact that hyper-recombination of thp1Δ cells is linked to transcription elongation is good evidence that these mutants have a transcription defect responsible for hyper-recombination. Nevertheless, to confirm that the lower rate of mRNA formation observed in time course kinetic experiments is not due to high rates of mRNA decay caused by thp1Δ, we determined the degradation rate of two mRNAs, GAL1 and lacZ, driven by the same regulated GAL1 promoter. For this, we first allowed cells to accumulate mRNA in 2% galactose. After repressing transcription by shifting cells to 2% glucose, the kinetics of degradation of the accumulated mRNA was determined in time course experiments. Whereas thp1Δ strains formed the GAL1 mRNA at half the wild-type rate (20Gallardo M. Aguilera A. Genetics. 2001; 157: 79-89Google Scholar), Fig. 3 shows that the rate of degradation of this mRNA was not higher in thp1Δ versus wild-type cells (half-lives of 17 and 12 min, respectively). Also, whereas thp1Δ cells, in contrast to wild-type cells, did not form detectable lacZ mRNA after3hof transcription activation (20Gallardo M. Aguilera A. Genetics. 2001; 157: 79-89Google Scholar), Fig. 3 shows that the rate of lacZ mRNA degradation was not higher in thp1Δ versus wild-type cells (half-lives of 7.5 and 4.5 min, respectively). We can therefore conclude that the strong defect in the kinetics of mRNA formation of thp1Δ cells is caused by defective transcription, and not by increased mRNA degradation.Fig. 3Kinetics of degradation of GAL1 and lacZ mRNAs in thp1Δ mutants. Shown are the results from Northern analysis of the mRNA decay of the endogenous GAL1 mRNA and the lacZ mRNA driven by the GAL1 promoter in cells transformed with p416-GAL1-lacZ. Mid-log phase wild-type (WT; W303-1A) and thp1Δ (WFBE046) cells grown in 2% galactose-containing SC medium either for 3 h (GAL1) or overnight (lacZ) were transferred to 2% glucose-containing SC medium before samples were taken at the indicated times. The 0.75-kb GAL1 PvuII-AvaI internal fragment, the 3-kb lacZ BamHI-BglII fragment, and the 589-bp 25 S rRNA internal fragment obtained by PCR were used as 32P-labeled DNA probes.View Large Image Figure ViewerDownload (PPT)Thp1p Binds RNA in Vitro—Because null mutants of THP1 show phenotypes similar to those of mutants of the THO/TREX complex, Nab2p, and mRNA export factors Mtr2p and Mex67p, all of which bind RNA (17Santos-Rosa H. Moreno H. Simos G. Segref A. Fahrenkrog B. Pante N. Hurt E. Mol. Cell. Biol. 1998; 18: 6826-6838Google Scholar, 19Jimeno S. Rondón A.G. Luna R. Aguilera A. EMBO J. 2002; 21: 3526-3535Google Scholar, 21Anderson J.T. Wilson S.M. Datar K.V. Swanson M.S. Mol. Cell. Biol. 1993; 13: 2730-2741Google Scholar, 37Strasser K. Hurt E. Nature. 2001; 413: 648-652Google Scholar), we investigated whether Thp1p associates with either RNA or DNA in vitro. We first purified His6-Thp1p from E. coli. RNA band shifting assays using a 90-nucleotide long RNA molecule showed that Thp1p bound RNA (Fig. 4A). Binding was directly proportional to the amounts of Thp1p used. No binding activity was observed with the negative control, i.e. purified material obtained from E. coli transformed with the empty vector pT7-7-His6. The ability to bind RNA is not conferred by the His6 tail because we have shown that other His6-tagged proteins did not bind RNA in our assays. 2A. G. Rondón and A. Aguilera, unpublished data. Fig. 4In vitro RNA and DNA binding assays of purified His-Thp1p.A, RNA binding assay using the